Animal knits for kids : 30 cute knitted projects they'll love - Berry, Amanda (Knitwear designer) (Barron's Educational Series, Inc., 2015)
"Babies and animals are a naturally adorable match and this book is bursting with animal-themed knits for little ones ages birth to 36 months. The various sections of the zoo-- from jungle and savannah to reptile house and polar region--serve as inspiration for these 30 projects. Whether it's a hippo-face rattle, bear-paw booties, a tiger-striped onesie, or a penguin bottle carrier, these bright, personality-filled projects will garner roars of approval! Inside, readers will find: 30 projects for knitters of all levels, includes items worked in flat and in the round; an essential guide to basic tools, techniques, and materials; notes on safety when knitting for young children; guidance for a variety of color work and finishing techniques. Most projects only require one skein of yarn per color to minimize costs and waste. Each project is given a rating based on skill level and time involved. More than 100 full-color illustrations, along with abbreviations, conversion charts, and other handy hints make Animal Knits for Kids a must-have addition to any knitter's library."--Amazon.com